1995
DOI: 10.1073/pnas.92.6.2249
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the zinc-finger gene PLZF at rhombomere boundaries in the vertebrate hindbrain.

Abstract: To investigate the potential biological role(s) of the PLZF gene, discovered as a fusion with the RARA locus in a patient with acute promyelocytic leukemia harboring a t(11;17) chromosomal translocation, we have isolated its murine homologue (mPLZF) and studied its patterns of developmental expression. The levels of mPLZF mRNAs increased perinatally in the liver, heart, and kidney, but with the exception of the heart, they were either absent or very low in the adult tissues. In situ analysis of mPLZF expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
75
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(77 citation statements)
references
References 30 publications
2
75
0
Order By: Relevance
“…Unfortunately, the precise role of PLZF remains unclear. PLZF is a Krüppel-like nuclear protein which is likely involved in central nervous system development (13,14,25,37,39). Although no physiologically relevant DNA-binding sites or target genes have yet been reported for PLZF, many features of PLZF are shared with known transcription factors; it is therefore possible that PLZF is indeed a transcription factor and can regulate gene expression by tethering directly or indirectly (through an intermediary protein) to DNA.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the precise role of PLZF remains unclear. PLZF is a Krüppel-like nuclear protein which is likely involved in central nervous system development (13,14,25,37,39). Although no physiologically relevant DNA-binding sites or target genes have yet been reported for PLZF, many features of PLZF are shared with known transcription factors; it is therefore possible that PLZF is indeed a transcription factor and can regulate gene expression by tethering directly or indirectly (through an intermediary protein) to DNA.…”
Section: Discussionmentioning
confidence: 99%
“…PLZF is a sequence-speci®c DNA binding transcriptional repressor di erentially expressed during embryogenesis and in adult tissues (Avantaggiato et al, 1995;Cook et al, 1995). PLZF is expressed in human CD34 + cells and in multipotent progenitor cell lines such as FDCPMixA4 and at lower levels in more di erentiated myeloid cell lines (Reid et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…In murine embryos, PLZF is expressed in the aorta-gonad-mesonephros region Cook et al, 1995), where the hematopoietic stem cells were found to emerge from (Godin et al, 1993;Medvinsky et al, 1993). The molecular pathways through which PLZF exerts its function are still under investigation.…”
Section: Introductionmentioning
confidence: 99%